2018
DOI: 10.1111/ijfs.13704
|View full text |Cite
|
Sign up to set email alerts
|

Effects of colorant concentration and ‘natural colour’ or ‘sodium content’ claim on saltiness perception, consumer liking and emotion, and purchase intent of dipping sauces

Abstract: Summary Natural colorant (no colorant, NC = 0%; moderate colorant, MC = 1.2%; high colorant, HC = 3.6% w/w) and salt (regular salt, RS = NaCl; reduced sodium, ReS = KCl; no salt, NS) were added in mayonnaise‐based dipping sauces to evaluate effects of colorant concentration and ‘natural colorant’ or ‘sodium content’ claim on saltiness expectation, consumer liking and emotion, and purchase intent (PI) of these products. Regardless of the salt type and content, increasing colorant concentration decreased colour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 41 publications
2
26
0
1
Order By: Relevance
“…Nowadays, consumers are more health conscious and demand more clean labels for their food products. The increased PI after the health benefit statement about the products was given to consumers was observed in previous studies (Poonnakasem et al., ; Sukkwai et al., ). In this study, additional product safety information was given to consumers as follows: (1) it was organic, (2) it was aflatoxin free, and (3) it was organic and aflatoxin free, then they rated PI once again.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Nowadays, consumers are more health conscious and demand more clean labels for their food products. The increased PI after the health benefit statement about the products was given to consumers was observed in previous studies (Poonnakasem et al., ; Sukkwai et al., ). In this study, additional product safety information was given to consumers as follows: (1) it was organic, (2) it was aflatoxin free, and (3) it was organic and aflatoxin free, then they rated PI once again.…”
Section: Resultssupporting
confidence: 72%
“…A group of Thai consumers ( n = 110: 43.6% males and 56.4% females) who regularly purchased and used chili powder were asked to select all relevant terms as evoked by chili powder using check‐all‐that‐apply (CATA) on a printed paper questionnaire. Selection criteria from previous studies required at least 20% frequency responses (King & Meiselman, ; Poonnakasem, Pujols, Chaiwanichsiri, Laohasongkram, & Prinyawiwatkul, ; Sukkwai et al., ; Wardy et al., ), whereas others suggested at least 10% frequency responses (Bhumiratana et al., ; Tepsongkroh et al., ). For this study, terms with at least 14% frequency responses were considered in order to include as many terms as possible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Food-evoked emotions can be related to distinguishable color schemes (Gilbert, Fridlund, & Lucchina, 2016) and mediate odorcolor correspondences (Schifferstein & Tanudjaja, 2004). Specific expectations of color are further related to sensory aspects such as flavor (Gilbert et al, 2016), and color may strongly influence product acceptability (Sukkwai et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Color influences consumer perceptions of flavor, liking, emotions, and overall perception and purchase intent . Chambers and Wolf suggested that ranking tests on visual evaluations might be less prone to fatigue than taste and aroma tests, possibly favoring a joint ranking (1SS) session.…”
Section: Introductionmentioning
confidence: 99%